Charles Brockden Brown - Ringe, Donald A. (Boston : Twayne Publishers, 1991)
Explores Charles Brockden Brown's formative role in American literature and the Gothic novel.
Includes bibliographical references (p. 132-137) and index.
Young Adult.
Young Adult
Keywords: Brown, Charles Brockden, -- 1771-1810 -- Criticism and interpretation; Brown, Charles Brockden, -- 1771-1810.